Pengaruh Leverage, dan Kebijakan Dividen Terhadap Nilai Perusahaan - Nabilah, Jihan; Khasanah, Uswatun; Nuryati, Tutty (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
Analysis of the theory behind how leverage and dividend policy affect business value is the main goal of this study. A quantitative strategy combined with a literature review method is used in this investigation. The theoretical underpinnings, additional explanatory factors, and research findings from earlier literature are presented in this study. Signaling theory is the underlying hypothesis of this investigation. Leverage and dividend policy are two further explanatory variables that are mapped to effect business value. These findings demonstrate a divergent link of leverage and dividend policy on firm value, making it impossible to come to a consensus. This study also offers a more thorough explanation of several current events and can help with studies looking at the effects of leverage and dividend policy on firm value.